Technology Training of Teachers to Work in Science Classes of Physical and Mathematical Profile - Федорчук, А. Л. (Educational Dimension, 2012)
Fedorchuk A.L. Technology Training of Teachers to Work in Science Classes of Physical and Mathematical Profile. The article deals with the peculiarities of preparation of future teachers science to work in specialized classes. Technology of preparing future professionals to work in school physics and mathematics account.